198 STERILE PLEURAL EMPYEMA IN A HUMAN IMMUNODEFICIENCY VIRUS-POSITIVE AND INJECTION DRUG USER MALE. (1st January 2005) - De Jesus-Monge, W. E.; Santos, R.; Serrano, J.; Cunningham, E.
Abstract : Pleural empyema is a collection of pus between the lungs and the chest wall. Approximately 50% of cases complicate pneumonia. It is a cause of significant morbidity and mortality despite appropriate antibiotic therapy and various options for drainage. The purpose of this report is to present the case of an human immunodeficiency virus (HIV)-positive and injection drug user male who presented with a unilateral apical sterile pleural empyema. A 36-year-old male, HIV-positive and chronic injection drug user, was admitted to our institution due to a left upper lobe lung mass seen by chest x-ray and chest pain. Left chest pain has been of 3 months of evolution, pressure-like, aggravated by deep inspiration and coughing. Patient was hospitalized 3 months before in the same institution due to a left leg cellulitis. Upon physical exam, patient is febrile with painful palpation in lower posterior left lung, decreased breath sounds throughout left lung field (worst in base) otherwise clear to auscultation bilaterally, and dull percussion in upper and middle posterior left lung field. Infectious foci and nosocomial infections were considered and he was treated intravenously with ceftriaxone and vancomycin. A soft tissue density in apical region of the left hemithorax suggestive of pleural or extrapleural origin, with increased opacification of the left upper lung parenchyma was seen during his previous hospitalization. A thorax computerized tomographic (CT) scan without contrast, performed during this hospitalization, showed a left-sided homogenously round structure with thick margins starting at the apicoposterior portion of the left upper lobe of lung. A CT-guided aspiration was performed, with almost complete resolution of the empyema. Pleural fluid was of exudative nature, with leukocytosis, no organism growth, no fungi, and no acid-fast bacilli. Two weeks after aspiration, the empyema was reaccumulating. A bronchoalveolar lavage was negative for malignancy, acid fast stain, and Grocott stain, without evidence of Actinomyces. The fact that the empyema was sterile may be explained by the long-term antibiotic therapy the patient received before samples were obtained. Pulmonary complications of HIV have been well studied, mainly caused by opportunistic infections due to their impaired immune function. Injection drug users are predisposed to a wide range of infectious processes. The pathophysiology, diagnosis, and management of this entity will be presented.